استراتیجیة التعلم التولیدي و فاعلیته فی التحصیل المعرفي و تنمیة أسالیب التعلم في مادة التاريخ - Hussien Saadi Ibrahim; Rezan Ali Ibrahim; Tanya Nooraldeen Sabir (QALAAI ZANIST JOURNAL, 2019)
The importance of this study is highlighted in the following: 1 - The importance of using the strategy of generative learning in the process of teaching, which is regarded as an effective strategy of learning that focuses on learners as the center of education process. 2. The research aims to activate the theoretical knowledge which develops learners’ thinking skills and planning to organize information. 3. The research presents a procedural model for experimenting with a different strategy in education instead of focusing on the usual method of teaching. 4. The research contributes to encouraging male and female teachers to use generative learning strategies in teaching since it helps students increase their performance and develop their learning methods. In order to achieve the goals and hypotheses of the research, the 11th grade female students were selected as the sample of the research. They were divided into two groups, one experimental who were taught according to generative learning strategy, and another were taught according to the usual method. After the equivalence of the two groups in a set of variables, the post-test of the research tools was applied after verifying their validity and stability. In the light of the results of the research, the researchers drew the following conclusions: 1. The use of generative learning has more positively influenced the achievement of the students of the eleventh grade in history subject than the usual way of learning. 2. The use of generative learning, in teaching history to the 11th grade students, has its own positive unique effectiveness and impact in learning methods compared to the usual method used. 3. The students of the experimental group, who were taught through using generative learning, have been more successful than the students of the current group, who were taught according to the usual learning method. 4 . The two groups (experimental - and current) showed their success in the post-test over the pre-test of the measure of learning methods.